2020
DOI: 10.14444/7026
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Commercially Available Cell-Based Allografts in a Rat Spinal Fusion Model

Abstract: Background: To evaluate the comparative abilities of commercially available, viable, cellular bone allografts to promote posterolateral spinal fusion. Methods: Human allografts containing live cells were implanted in the athymic rat model of posterolateral spine fusion. Three commercially available allogeneic cellular bone matrices (Trinity Evolution, Trinity ELITE and Osteocel Plus) were compared with syngeneic iliac crest bone as the control. All spines underwent radiographs, manual palpation, and micro-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, Russell et al [35] found large variations in fusion rates (0-100%) for seven commercially-available DBM products using a rat postero-lateral spinal fusion model, with two products yielding a 0% fusion rate by manual palpation and lack of evidence of bone bridging by micro-computed tomography. Similarly, Johnstone et al [36], using the same postero-lateral spinal fusion model, reported fusion rates of 7%, 71% and 77% for three commercially-available CBM allograft products. These findings suggest that more highly manipulated bone allografts exhibit greater variability in clinical performance than minimally manipulated mineralized structural bone allografts [37].…”
Section: Discussionmentioning
confidence: 81%
“…For example, Russell et al [35] found large variations in fusion rates (0-100%) for seven commercially-available DBM products using a rat postero-lateral spinal fusion model, with two products yielding a 0% fusion rate by manual palpation and lack of evidence of bone bridging by micro-computed tomography. Similarly, Johnstone et al [36], using the same postero-lateral spinal fusion model, reported fusion rates of 7%, 71% and 77% for three commercially-available CBM allograft products. These findings suggest that more highly manipulated bone allografts exhibit greater variability in clinical performance than minimally manipulated mineralized structural bone allografts [37].…”
Section: Discussionmentioning
confidence: 81%
“…The second study compared Trinity Evolution, Trinity ELITE, Osteocel Plus, and syngeneic ICBG. 14 By manual palpation over the grafted area, Trinity Evolution and Trinity ELITE allografts demonstrated the highest fusion rates, at 71% (10/14) and 77% (10/13), respectively. Osteocel Plus showed a significantly lower fusion rate than both Trinity products at 7% (1/14).…”
Section: Studies Comparing Acbm Productsmentioning
confidence: 93%
“…All human clinical studies and animal research in which ACBMs were used as bone substitutes or BGEs and where clinical and/or radiological outcome data were provided were included. The final 18 selected articles for the systematic review included 5 publications pertaining to animal research, [11][12][13][14][15] 5 publications pertaining to ACBM use in cervical spine surgery in human subjects, [16][17][18][19][20] and 8 publications pertaining to ACBM use in lumbar spine surgery in human subjects. [21][22][23][24][25][26][27][28] Tables 2 and 3 detail the study characteristics, patient profiles, and study outcomes for ACBM use in human clinical studies in cervical spine and lumbar spine surgery, respectively.…”
Section: Pubmed Search and Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Trinity Elite, developed by Orthofix Medical Inc, is one such cellular-based autograft (CBA) consisting of viable cancellous bone with demineralized cortical bone and osteogenic cells. Trinity in patients undergoing foot and ankle arthrodesis with comorbidities provide comparable or greater fusion rates than autograft, 7 , 8 and both animal model 6 , 9 and limited clinical studies have shown that it can be safely used for fusions involving the cervical 10 , 11 and lumbar 12 13 14 spine. However, limited evidence exists directly comparing fusion rates with Trinity with other bone graft alternatives.…”
mentioning
confidence: 99%